Odpowiedzi

2009-05-13T22:35:47+02:00
A) (1+√2)+(1-√2)=2+2√2
(1+√2)-(1-√2)=1+√2-1+√2=2√2
(1+√2)*(1-√2)=1-√2+√2-2
(1+√2)/(1-√2)=1-√2+√2-1=0

b) (1+√5)+(3-2√5)=4-√5
(1+√5)-(3-2√5)=-2+3√5
(1+√5)*(3-2√5)=3-2√5+√5-10=-7-2√5+√5
(1+√5)/(3-2√5)=

c) (2+√7)+(1-√7)=3
(2+√7)-(1-√7)=1+2√7
(2+√7)*(1-√7)=2-2√7+√7+7=9-2√7+√7
(2+√7)/(1-√7)=
2009-05-13T22:41:00+02:00
A) a=1 + √2
b=1-√2

a+b=2 ,
a-b=2√2 ,
a *b=(1 + √2)(1-√2)=1-2=-1,
a /b=(1 + √2)/(1-√2)=(1 + √2)²/(-1)=-3-2√2

b)a=1+√5
b=3-2√5

a+b=4-√5,
a-b=-2+3√5 ,
a *b=(1 + √5)(3-2√5)=-7+√5,
a /b=(1 + √5)/(3-2√5)=(1 + √5)(3+2√5)/(-11)=(13+5√5)/(-11)

c)a=2+√7
b=1-√7

a+b=3,
a-b=1+2√7 ,
a *b=(2 + √7)(1-√7)=-5-√7,
a /b=(2 + √7)/(1-√7)=(2+ √7)(1+√7)/(-6)=(9+3√7)/(-6)